2020
DOI: 10.1111/1911-3846.12522
|View full text |Cite
|
Sign up to set email alerts
|

Directors' Informational Role in Corporate Voluntary Disclosure: An Analysis of Directors from Related Industries

Abstract: Boards of directors play their role in corporate governance by advising and/or monitoring managers. In the corporate disclosure literature, prior research has documented directors' monitoring role, yet empirical evidence on directors' advising role is limited. Since the advising role often entails information transfer, we examine directors who concurrently serve as directors or executives in the firms' related industries (DRIs) and hence possess valuable information about the firms' external operating environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Second, prior studies have shown that having common directors on the boards facilitates information sharing (e.g., Ke et al 2019). Thus, we expect that when the supplier and the customer share one or more directors the customers' private information acquisition costs will be lower.…”
Section: Private Information Acquisition Costsmentioning
confidence: 88%
See 1 more Smart Citation
“…Second, prior studies have shown that having common directors on the boards facilitates information sharing (e.g., Ke et al 2019). Thus, we expect that when the supplier and the customer share one or more directors the customers' private information acquisition costs will be lower.…”
Section: Private Information Acquisition Costsmentioning
confidence: 88%
“…Second, we find that the negative association between customer concentration and management forecasts is more pronounced when the costs of customers' private information acquisition are low. We measure the cost of private information acquisition with the duration of the customer-supplier relationship (Patatoukas 2012), the existence of common directors (Ke et al 2019), and the geographical distance between the supplier and customers (Agarwal and Hauswald 2010). Third, we show that the negative relation between customer concentration and management forecasts is stronger for firms whose customers have lower costs of finding a different supplier, measured with the supplier's market share in its 4-digit SIC industry (Dhaliwal et al 2015).…”
mentioning
confidence: 86%
“…However, these benefits may come at a cost; for example, board interlocks might propagate value decreasing practices, or well-connected directors may be too busy to act as good monitors and advisors to the firm (Erel et al 2021). Studies in our review that examine the consequences of director networks document a positive association with firm performance (Larcker et al 2013), strategic advising (Brown et al 2019), financial reporting quality (Intintoli et al 2018), and management forecast accuracy (Ke et al 2020;Schabus 2022). Furthermore, some studies document that director networks have a positive effect on capital markets, including the likelihood of private equity transactions (Stuart and Yim 2010;Rousseau and Stroup 2015), sophisticated investors' trading patterns (Akbas et al 2016), and M&A deals (Cai and Sevilir 2012;Ishii and Xuan 2014).…”
Section: Whole Board Networkmentioning
confidence: 90%
“…To test this spillover effect, we follow Ke, Li, and Zhang (2020) to use input-output table relationships to identify the supply chain industry of the firm's industry and then, calculate the average digitization degree mean SupplyChain_DigitalW (SupplyChain_DigitalS) of firms in the supply chain. As shown in columns (3) and (4) of Table 10, the coefficients for SupplyChain_DigitalW and SupplyChain_DigitalS are both significantly positive after controlling for the firm's own digital development, suggesting a positive spillover effect of enterprise development in the supply chain.…”
Section: Spillover Effects Of Firms' Digital Developmentmentioning
confidence: 99%